Penerapan Model Team Accelerated Instruction dalam Meningkatkan Keterampilan Membaca Menggunakan Media Microsoft Office Powerpoint di Sekolah Dasar - Rahmatiah Rahmatiah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: Application of Team Accelerated Instruction Model in Improving Reading Skills Using Microsoft Office Powerpoint Media in Elementary Schools. This study aims to describe the Team Accelerated Instruction method in improving reading skills andusing literacy in elementary schools. This type of research is class action research consisting of two cycles in which each cycle is held one meeting. Research procedures include, planning, execution of actions, observation, and reflection. The subjects in this study were 17 grade V students of Public Elementary School 1, Sidenreng Rappang Regency consisting of 10 male students and 7 female students. The results showed that the Team Accelerated Instruction method in improving reading skills m using media microsoft office powerpoint in elementary schools. The results were based on student learning outcomes in cycle I, with the lowest score of 70, the highest score of 90, the average score of 6.67, and classical completeness of 64%. In the implementation of cycle II, data were obtained with the lowest value of 75, the highest value of 100, the average value of 8.3 and classical completeness of 94%.